Balanced Scorecard Approach in Strategic Decision Making in Development of Executive Clinic Universitas Trisakti Academic Dental Hospital 2023 – 2027 - Meliani, Meliani; Astoeti, Tri Erri; Yusra, Yohana (Universitas Diponegoro, 2024)
Strategic planning enables hospitals to anticipate various ever-changing conditions and provides a roadmap, direction, and means to achieve their goals. The Executive Clinic at RSGM-P FKG USAKTI is a comprehensive and professional healthcare provider offering specialized and public services. However, its role as a profit center has experienced a decline during the two-year pandemic. This research aims to revitalize the Executive Clinic as a profit center for RSGM-P FKG USAKTI. The research methodology employed is operational research. The strategic plan development involves three stages: input, matching, and decision stages. The findings from the research indicate that the input stage resulted in the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices with scores of 2.81 and 2.69, respectively. The matching stage utilized the SWOT matrix and IE matrix, recommending the